A New Remote Control for Traceless meta‐CH Olefination of Phenols. Issue 12 (9th September 2013) - Martínez, Claudio; Muñiz, Kilian
<x xml:space="preserve">Abstract</x> Ghosting the directing group: A clever design of a nitrile based catalyst directing group, serves as tool in the palladium‐catalyzed meta‐olefination of phenol derivatives. This group can be removed tracelessly, thus providing a convenient route to meta‐substitution of phenols, a transformation that cannot be conducted by classic aromatic substitution chemistry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>